Level of Satisfaction of Customers on the Use of E-Commerce of Food Establishments - Barrera, Janet D.; Samos, Beverly B.; Barrios , Mary Rose (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study aimed to investigate the level of satisfaction on the use of e-commerce to customers of food establishments in Dipolog City amidst the CoVid19 pandemic this academic year 2021-2022. Specific questions were answered, namely: the profile of the respondents in terms of age, sex, educational attainment, civil status, occupation, and type of gadget used; the level of satisfaction of the respondents on the use of e-commerce in terms of e-marketing, platforms, and customers’ feedback; test for the significant difference in the level of satisfaction of the respondents on the use of e-commerce when analyzed according to their profile; the problems met or challenges encountered in the use of e-commerce; and test for the significant relationship between the respondents’ level of satisfaction and the problems met or encountered on the use of e-commerce. This study used the descriptive quantitative correlational method of research utilizing questionnaire as its principal tool of gathering data. The study was conducted among 193 residents of different barangays in Dipolog City during the calendar year 2022. The researcher-made questionnaire was used. Items of the questionnaires were gathered from the readings of the literature on e-commerce. The questionnaire was subjected for content and construct validity using Cronbach’s Alpha test to measure the internal consistency of the questionnaire. The statistical analysis of the data included the use of frequency counting and percentage, weighted average mean and standard deviation. Tests of inference were done using the t-test, Kruskal-Wallis test and the Spearman rho correlation coefficient. Statistical analyses were run using the SPSS and online data analysis calculators. The majority of the respondents belonged to age brackets 33-47 years old with 102 or 52.85 percent from the 193 respondents, mostly females, college graduate, married, working in the government, and used cellular phones. Most of the respondents were highly satisfied on the use of applications and platforms as these lead to prompt and on-time food delivery. There is no significant difference in the level of satisfaction when grouped according to age, sex, educational attainment, civil status, occupation, and type of gadget used. The use of e-commerce may not be the crucial factor affecting their problems and challenges. Concerned agencies may look into their policies of providing regulations. Future researches may be conducted to look into other factors that may have impact on the satisfaction level of the consumers in the food industry.